The application of solar technologies for sustainable development of agricultural sector - Mekhilef, Saad; Faramarzi, S.Z.; Saidur, Rahman; Salam, Z. (Elsevier, 2013)
Solar energy is one of the cleanest sources of alternative energy. Due to high energy demand in one hand and environmental negative impact of fossil fuels, on the other hand, many countries consider the alternative energy sources as a suitable and feasible option in industry and domestic usage. It was discovered that the different applications of solar energy in industries are being accepted more than ever. The present study is a state of art on the numerous new and feasible technologies of solar energy applications in the agricultural sectors. It discusses about the importance of solar energy as environmental clean technologies and the most reliable energy source. This study covers different types of solar energy systems like as solar photovoltaic and solar thermal for pumping water, drying crops, cooling the storages and producing heating/cooling greenhouses. It has been proven that photovoltaic systems and/or solar thermal system would be the suitable options in agricultural application and especially for the distant rural area.